2016
DOI: 10.4102/ojvr.v83i1.1013
|View full text |Cite
|
Sign up to set email alerts
|

Taeniasis in non-descript dogs in Ngorongoro, Tanzania: Prevalence and predisposing factors

Abstract: The prevalence of taeniasis was determined during the period January to April 2013 in a cross-sectional study of non-descript domestic dogs from the livestock–wildlife ecosystem of Ngorongoro, Tanzania. Taeniid eggs were determined by screening faecal samples using the formalin-ether sedimentation technique. Predisposing factors for dog infection were assessed in relation to demographic, husbandry and management data. Of the 205 faecal samples screened, 150 (73.2%) were positive for taeniid eggs. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…Although the prevalence was lower compared to the findings by Ernest et al . [ 25 ], still the prevalence suggests the possibility that hydatidosis is of public health importance in this study area and that some of the taeniid eggs recovered from the feces of dogs in the previous study may be eggs of Echinococcus species [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence was lower compared to the findings by Ernest et al . [ 25 ], still the prevalence suggests the possibility that hydatidosis is of public health importance in this study area and that some of the taeniid eggs recovered from the feces of dogs in the previous study may be eggs of Echinococcus species [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low taeniid prevalence of 0.25% among domestic dogs in Europe (Dyachenko et al, 2008); 5.6% among stray dogs in Iran (Kohansal et al, 2017) and 8.0% among sheep dogs in England (Phythian et al, 2018) have been reported. However, higher prevalence of 11.07 % among stray dogs in Iran (Mirbadie et al, 2018); 14.9 % among dogs from farming communities in Uganda (Oba et al, 2016); 34.4% among farm dogs in China (Guo et al, 2014); 56.7 % among trade dogs in Plateau State, Nigeria (Karshima et al,2017); and 73.2% among village dogs with presence of slaughter slabs in Tanzania (Swai et al, 2016) have also been reported. The low prevalence of taeniid infection obtained in this study may be because the dogs were owned and mostly as pets or for security.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of taeniid infection obtained in this study may be because the dogs were owned and mostly as pets or for security. Street roaming (Swai et al, 2016), access to cysts of taeniidae in intermediate hosts (Oba et al, 2016) and poor or lack of deworming (Swai et al, 2016) have been associated with increase prevalence of taeniid infection. Though, taeniid infection was low among owned dogs in Ibadan, its prevalence calls for adequate attention to regular proper deworming of owned dogs and other preventive measures in order to prevent accidental infection in their owners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(87%) was also observed in stray dogs from Kalar city of Sulaimani province (north governorate of Iraq) [44]. Studies conducted in other countries where taeniid tapeworms are endemic have also reported high prevalences: for example 34.4% in farm dogs from Xinghai county of Qinghai Province of China that attributed to neglect deworming dogs with praziquantel and lack of education programme to the dogs owners [45]; and 73.3% in domestic dogs from Ngorongoro (northern Tanzania) which are attributed to less awareness of the dog owners toward proper management and practices of their animals [46].…”
Section: Discussionmentioning
confidence: 99%